NEW CONSERVATIONIST SYSTEM SEEDING FOR SMALL FARMS WITH MULTIFUNCTIONAL NEW DRAGON - ALBIERO, Daniel; MACIEL, Antonio José da Silva (Revista Brasileira de Engenharia de Biossistemas, 2010)
The small farms have a important place in brazilian agriculture, it is being responsible for larger production of foods in Brazil. However the small farmers not have specific equipments for seeding in good quantities. The subject this paper was the development of a new conservationist seeding system adapted for small farms through the construction a new multifunctional seeder with Rotative Paraplow. This new seeder wad tested in field in real conditions. The results showed that the prototype have a good performance in soybean seeding, with operation easy, little maintenance, and mainly adapted at operational needs from small farms.